The Representation of Women’s Oppression in Joyce Lebra’s the Scent of Sake: A Feminism Study - Christ Tantya Wahyuni (Fakultas Ilmu Budaya, 2016)
This thesis analyzes some issues related to the representation of women’s oppression in a cultural and historical Japan set novel The Scent of Sake. Until now, women’s oppression still becomes one of the most discussed topic that have not found the concrete solution to end it yet. Women still become the object of discrimination, exploitation, humiliation and other forms of oppression in the society. Considering such aspect, women’s oppression is chosen as my topic in the research because I want to know the forms of oppression that exist in the society. There are three specific goals of this study. The first goal is to explore the representation of women’s oppression in the novel. The second goal is explore the representation of feminism discourse through the female main characteristics and actions. The last goal is to find out the critical position of the author. By using Stuart Hall’s theory of representation and Michel’s Foucault discursive approach, I elaborate the ways of the author delivers the discourse of women’s oppression in the novel. Through the novel, the author represents the discourse of women’s oppression. There are three kinds of oppression experienced by the main character: the restrictions in learning and running the business, domestic violance, and mental/psychological abuse. Furthermore, I also elaborate the representation of feminism discourse through the main character in getting her freedom and equality. There are three kinds of actions and characteristics of the main character that reflects the discourse of feminism: financially independent, confessing her love, and educated. By using Stuart Hall’s theory of representation that focuses on constructionist approach, I analyze the critical position of the author. As an American, Joyce Lebra wants to tell the reader that the patriarchal culture in Japan is such an oppression toward women. Thus, she created Rie Omura’s character that suffers from the restrictions and humiliation given to her by her family and husband. Lebra also delivers her opinion about what should women do when they face such discrimination and oppression through Rie’s characteristics and actions. The result of this study shows that the society in America helps Lebra constructing her opinion about women in Japan. Through Rie’s character who suffers from the patriarchal culture, Lebra thought that women should be given the freedom and opportunities as how women are treated in America. Therefore, she also created Rie’s character that behave against the mainstream culture to liberate herself from the oppression. Rie is described as a woman who fought for the independence and freedom. She educated herself, confessed her love, and was financially independent. As Hall stated that the social actors use language to represent their concept of things, through The Scent of Sake, Joyce Lebra wishes to free women from oppressive gender roles – that is, from those roles used as excuses or justifications for giving women unfair treatments in the society. thus, it can be said that she is under individual or liberal feminism.
reupload file repositori 11 mei 2026_kurnadi/citra :: Finalisasi file repositori 15Juni2026_Kurnadi
Keywords: Women’s Oppression; Joyce Lebra’s